2003
DOI: 10.1614/0890-037x(2003)017[0157:rogrro]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Response of Glufosinate-Resistant Rice (Oryza sativa) to Glufosinate Application Timings1

Abstract: At 14 d after treatment (DAT), glufosinate-resistant CPRS PB-13 rice was injured with early- and late-season glufosinate applications in 1998 and 1999. At 35 DAT, injury was less than 5%. Glufosinate delayed CPRS PB-13 heading by 7 to 15 d and reduced plant height at harvest but did not affect grain moisture and yield compared with the nontreated CPRS PB-13. But yield was reduced compared with conventional Cypress. At 14 DAT, glufosinate-resistant BNGL HC-11/62 rice was injured with early- and late-season appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The majority of these differences have been agronomic traits. Lanclos et al (2003) reported that two transformed glufosinate-tolerant lines of rice (BNGL HC-11 and BNGL HC-62) were shorter and had lower grain moistures at harvest compared with their parent line when glufosinate was not applied. An additional transgenic rice line, CPRS PB-13, was taller and produced lower yields than its parent line in the absence of glufosinate application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of these differences have been agronomic traits. Lanclos et al (2003) reported that two transformed glufosinate-tolerant lines of rice (BNGL HC-11 and BNGL HC-62) were shorter and had lower grain moistures at harvest compared with their parent line when glufosinate was not applied. An additional transgenic rice line, CPRS PB-13, was taller and produced lower yields than its parent line in the absence of glufosinate application.…”
Section: Discussionmentioning
confidence: 99%
“…Few experiments that include a nontreated transgenic control have examined the effects of herbicide-tolerant transgenic varieties on insects, although this type of evaluation of agronomic characteristics of transgenic varieties is required by governmental agencies. Such studies have shown that glufosinate applications to BNGL HC-11, BNGL HC-62, and CPRS PB-13 at various timings produced shorter plants and increased number of days required to reach 50% panicle emergence relative to their respective nontreated controls (Lanclos et al 2003). Herbicide applications to transformed (sulfonylurea-tolerant) tobacco lines increased sucker growth by 1.7Ð 8.5 times, depending on the line, herbicide, and herbicide rate (Brandle and Miki 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weeds present a constant problem in rice (Oryza sativa L.) production and can reduce rice yield with early season competition [1,2]. e lack of weed control can reduce rice yield over 90%; therefore, effective weed management programs are essential for maximizing rice production [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Glufosinate has been evaluated for weed control in glufosinate-resistant rice for years (Braverman and Linscombe 1994;Lanclos et al 2002;Sankula et al 1997aSankula et al , 1997bWheeler et al 2000). Postemergence application of glufosinate provides effective control of most weeds, including red rice (Oryza sativa L.), which may not be controlled in conventional rice production systems, with little injury to glufosinate-resistant rice (Lanclos et al 2003).…”
Section: Introductionmentioning
confidence: 99%